A new metaphor-less simple algorithm based on Rao algorithms: a Fully Informed Search Algorithm (FISA) - Ghasemi, Mojtaba; Rahimnejad, Abolfazl; Akbari, Ebrahim; Rao, Ravipudi Venkata; Trojovský, Pavel; Trojovská, Eva; Gadsden, Stephen Andrew (PeerJ. Computer science, 2023)
Many important engineering optimization problems require a strong and simple optimization algorithm to achieve the best solutions. In 2020, Rao introduced three non-parametric algorithms, known as Rao algorithms, which have garnered significant attention from researchers worldwide due to their simplicity and effectiveness in solving optimization problems. In our simulation studies, we have developed a new version of the Rao algorithm called the Fully Informed Search Algorithm (FISA), which demonstrates acceptable performance in optimizing real-world problems while maintaining the simplicity and non-parametric nature of the original algorithms. We evaluate the effectiveness of the suggested FISA approach by applying it to optimize the shifted benchmark functions, such as those provided in CEC 2005 and CEC 2014, and by using it to design mechanical system components. We compare the results of FISA to those obtained using the original RAO method. The outcomes obtained indicate the efficacy of the proposed new algorithm, FISA, in achieving optimized solutions for the aforementioned problems. The MATLAB Codes of FISA are publicly available at https://github.com/ebrahimakbary/FISA.
Keywords: Rao algorithms; Fully Informed Search Algorithm (FISA); Optimization; Constrained engineering optimization